Batik Motif Mathematical Modeling of the Spread of Malaria in Mimika Regency - Abada, Aka Nur Alya; I’zzah, Laila Rohmatul; Azzahra, Carissa Fisa; Sugiyanto, Sugiyanto (Proceeding International Conference on Religion, Science and Education, 2026)
This study aims to construct a batik motif inspired by the dynamics of malaria transmission through a SEIRS (Susceptible–Exposed–Infected–Recovered–Susceptible) mathematical modeling approach in Mimika Regency. The SEIRS model is used to represent the malaria transmission process, taking into account births, deaths, treatment in the exposed class, and the likelihood of recovered individuals becoming susceptible to infection again. Based on simulation results from the SEIRS model using data from the Mimika Regency Health Office in 2018, the basic reproduction number was obtained as 0.09, indicating that the spread of malaria tends to decrease and does not significantly cause new infections. This value is then translated into visual elements of batik through a dynamic balance pattern between four population classes (S, E, I, R) depicted as transitions in repetitive shapes and rhythms. The resulting motif represents the relationship between the stability of biological systems and visual harmony in batik art, reflecting the collaboration between science and local culture as an educational approach to public health issues.